Open Source Democracy: How online communication is changing offline politics - Rushkoff, Douglas, 1961- (Salt Lake City, UT : Project Gutenberg, 2004)
"Open Source Democracy: How online communication is changing offline politics" by Douglas Rushkoff is a thought-provoking exploration of how the rise of interactive media and the internet has transformed the political landscape. Written in the early 21st century, the book functions as a scientific publication that delves into the interplay of technology and democracy, showcasing the potential for online communication to foster civic engagement and reshape political narratives. Throughout the book, Rushkoff examines the implications of interactive technology on societal structures and communication. He argues that traditional narratives propagated by mainstream media are increasingly challenged by diverse viewpoints emerging from the internet. The text illustrates how online platforms enable citizens to bypass traditional gatekeepers and engage directly in political discourse, fostering a new cooperative ethos that promotes democracy. By analyzing historical narratives and current events, including the impacts of globalization and the attention economy, Rushkoff advocates for an open-source approach to democracy, where individuals can collaboratively shape their societal context and address contemporary challenges in an interconnected world. (This is an automatically generated summary.)
Release date is 2004-01-01
Keywords: Democracy; Information society; Information society -- Political aspects; Information technology -- Political aspects; Political participation